ECONOMIC REFORMS IN TIMOR LESTE: BETWEEN ECONOMIC GROWTH, EASE OF DOING BUSINESS AND INEFFECTIVE GOVERNMENT - Devi, Mely (PEOPLE: International Journal of Social Sciences, 2017)
Despite of its growing Gross National Income (GNI) per capita in the recent years, Timor Leste is still being classified as an economically fragile country for consecutive years by some international organizations. This research was then conducted within the purpose to understand the reasons behind such classification, by focusing on the relation between poverty, unemployment, government ineffectiveness, as well as the ease of doing business in the country. By using the secondary data provided by some notable international organizations, the research found out that all factors mentioned above are interrelated to each other, which consequently influence the economic fragility in Timor Leste, regardless of how growing their GNI per capita is. At the end of the research, certain recommendations are also proposed, in order to solve the problem of economic fragility in Timor Leste.